Marshall's dilemma and commercialization of European research - Edward Bergman (European Regional Science Association (ERSA), 2010)
Difficulty in extracting scientific and research findings from EU universities and placing such knowledge at the commercial disposal of innovation-dependent firms and industries is a cause for grave concern by the European Commission and many of its member states and regions, particularly when contrasted with the notable success enjoyed by U.S. universities. A review of literature from the perspective of EU knowledge-seeking firms and knowledge-generating universities reveals a striking asymmetry: firms presently seek mainly public science outputs, while universities pursue proprietary science opportunities more heavily in their dealings with business and industry. At the same time knowledge flows are being promoted far more aggressively, universities are being totally restructured, harmonised in many respects and decentralized regarding governance and accountability. Results from a web-survey of 1798 EU academics posted in Europe's universities listed in the Shanghai TOP 500 reveal several important findings of interest. First, EU and U.S. respondents have quite similar views of what is considered reasonable with regard to public vs. private science. The exceptions reveal a generally stronger approval by EU academicians for their universities to be more proactive regarding commercialization, particularly university support of research-based start-up firms, with some differences based on respondents' discipline [(1) biological sciences, 2) physics, 3) computer science, 4) chemical engineering, 5) economics and 6) history]. Further investigation shows those who have already undertaken or investigated commercialization opportunities tend to approve a battery of commercialization measures taken by their universities, and those who: a. have worked on externally-funded research projects with colleagues from industry, b. see regional business leaders influencing university commercialization policies, c. are heavily engaged in public service activities, and have collaborated with industry colleagues on research projects. (submitted to Uddevalla)
Keywords: 330